Plasma profile of pro‐inflammatory cytokines and chemokines in cocaine users under outpatient treatment: influence of cocaine symptom severity and psychiatric co‐morbidity. (22nd May 2014) - Araos, Pedro; Pedraz, María; Serrano, Antonia; Lucena, Miguel; Barrios, Vicente; García‐Marchena, Nuria; Campos‐Cloute, Rafael; Ruiz, Juan J.; Romero, Pablo; Suárez, Juan; Baixeras, Elena; de la Torre, Rafael; et al.
Abstract The treatment for cocaine use constitutes a clinical challenge because of the lack of appropriate therapies and the high rate of relapse. Recent evidence indicates that the immune system might be involved in the pathogenesis of cocaine addiction and its co‐morbid psychiatric disorders. This work examined the plasma pro‐inflammatory cytokine and chemokine profile in abstinent cocaine users (n = 82) who sought outpatient cocaine treatment and age/sex/body mass‐matched controls (n = 65). Participants were assessed with the diagnostic interview Psychiatric Research Interview for Substance and Mental Diseases according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM‐IV‐TR). Tumor necrosis factor‐alpha, chemokine (C‐C motif) ligand 2/monocyte chemotactic protein‐1 and chemokine (C‐X‐C motif) ligand 12 (CXCL12)/stromal cell‐derived factor‐1 (SDF‐1) were decreased in cocaine users, although all cytokines were identified as predictors of a lifetime pathological use of cocaine. Interleukin‐1 beta (IL‐1β), chemokine (C‐X3‐C motif) ligand 1 (CX3CL1)/fractalkine and CXCL12/SDF‐1 positively correlated with the cocaine symptom severity when using the DSM‐IV‐TR criteria for cocaine abuse/dependence. These cytokines allowed the categorization of the outpatients into subgroups according to severity, identifying a subgroup of severe cocaine users (9–11 criteria) with increased prevalence of co‐morbid psychiatric disorders [mood (54%), anxiety (32%), psychotic (30%) and personality (60%) disorders]. IL‐1β was observed to be increased in users with such psychiatric disorders relative to those users with no diagnosis. In addition to these clinical data, studies in mice demonstrated that plasma IL‐1β, CX3CL1 and CXCL12 were also affected after acute and chronic cocaine administration, providing a preclinical model for further research. In conclusion, cocaine exposure modifies the circulating levels of pro‐inflammatory mediators. Plasma cytokine/chemokine monitoring could improve the stratification of cocaine consumers seeking treatment and thus facilitate the application of appropriate interventions, including management of heightened risk of psychiatric co‐morbidity. Further research is necessary to elucidate the role of the immune system in the etiology of cocaine addiction.